2017
DOI: 10.1136/vr.104224
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor descriptions of veterinary student performance in the clinical workplace: a qualitative interview study

Abstract: This qualitative study investigated the qualities of veterinary student performance that inform a supervisor's impression of their competency. Semi-structured interviews were conducted with a purposive sample of 15 supervisors from different veterinary subdisciplines, to elicit descriptions of excellent, weak and marginal students. Thematic analysis of transcriptions revealed 12 themes, of which engagement was frequently discussed and of stated importance, and trustworthiness was a differentiator of weak and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…Preceptor evaluation of senior student clinical performance is, arguably, the best measure of global competence and employability available to the university educator. In addition to the ability to demonstrate and apply relevant knowledge and skills in an authentic environment, this evaluation technique assesses many non‐cognitive and affective domain skills that are strongly related to competence . Most notably, appropriate communication and interpersonal skills are likely assessed both at interview and in the final‐year clinical performance, perhaps explaining the relationship between the two.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preceptor evaluation of senior student clinical performance is, arguably, the best measure of global competence and employability available to the university educator. In addition to the ability to demonstrate and apply relevant knowledge and skills in an authentic environment, this evaluation technique assesses many non‐cognitive and affective domain skills that are strongly related to competence . Most notably, appropriate communication and interpersonal skills are likely assessed both at interview and in the final‐year clinical performance, perhaps explaining the relationship between the two.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the ability to demonstrate and apply relevant knowledge and skills in an authentic environment, this evaluation technique assesses many non-cognitive and affective domain skills that are strongly related to competence. 27 Most notably, appropriate communication and interpersonal skills are likely assessed both at interview and in the final-year clinical performance, perhaps explaining the relationship between the two. High written application scores are likely reflective of motivation, initiative and a strong work ethic, factors also likely to be rewarded in preceptor evaluation of student performance.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects of performance mirror the thematic content of two prominent themes found in a recent qualitative study of supervisor descriptions of excellent and weakly performing veterinary students that was conducted in the same context as the study reported here. 16 In the qualitative study, engagement (a student's enthusiasm for and participation in the activities of the placement) was the most commonly referred to aspect of student performance, and was frequently discussed irst or of stated importance to supervisors. Trustworthiness was notable as a diferentiator of excellent and weak performance of veterinary students.…”
Section: Discussionmentioning
confidence: 99%
“…However, qualitative research suggests that supervisors do consider multiple aspects of performance during evaluation and that these are distinct and independent, although related. [11][12][13][14][15][16][17] The one previously published study of the dimensionality of a veterinary in-training evaluation found that three dimensions were being evaluated by supervisors. 18 Other qualitative work suggests that a higher-order structure may be present as supervisors consider overarching and holistic factors as well as individual aspects of competency.…”
Section: Introductionmentioning
confidence: 99%
“…6 This means multiple types of interaction are required on a daily basis. Communication is a key RCVS day one competency 7 and is a well-known foundation for good practice, [8][9][10][11][12][13] yet a predominant number of complaints to the RCVS regarding veterinary surgeons involve communication issues. 14 An additional workforce concern for the profession is the forthcoming exit from the EU.…”
Section: Introductionmentioning
confidence: 99%